28t-10=14t-6

Simple and best practice solution for 28t-10=14t-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 28t-10=14t-6 equation:


Simplifying
28t + -10 = 14t + -6

Reorder the terms:
-10 + 28t = 14t + -6

Reorder the terms:
-10 + 28t = -6 + 14t

Solving
-10 + 28t = -6 + 14t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-14t' to each side of the equation.
-10 + 28t + -14t = -6 + 14t + -14t

Combine like terms: 28t + -14t = 14t
-10 + 14t = -6 + 14t + -14t

Combine like terms: 14t + -14t = 0
-10 + 14t = -6 + 0
-10 + 14t = -6

Add '10' to each side of the equation.
-10 + 10 + 14t = -6 + 10

Combine like terms: -10 + 10 = 0
0 + 14t = -6 + 10
14t = -6 + 10

Combine like terms: -6 + 10 = 4
14t = 4

Divide each side by '14'.
t = 0.2857142857

Simplifying
t = 0.2857142857

See similar equations:

| H=8-9.4j | | 4(x+8)+2x=42+5x | | 2/3x-1=5-2x | | -2.6549x=14.86744 | | -5(2+x)=-3(-4-2x) | | -2.6549=14.86744 | | -(r-2)+1=3(r+1) | | 17-22=-5x | | (5w^2)+(12w^2)= | | 3(4r+4)-r=45 | | 5t^2-10t=-4 | | 6x+35x=x | | -3.6x=-7.2 | | -3(x+2)-(2x-5)=-(5x+1) | | 5(2X+6)=4(5+2X)+3X | | -182=26x | | 2n+3(n+3)=21 | | -6x+9+x=-36 | | -29-7x=-7(x+5) | | 2(x+6)+7x=9x-12 | | G=8h/e | | -8x+8+6=-10-4x | | x=(12.2/4.00)*8.00 | | 12=-6-k | | -8(x-8)=12+5x | | -14-6x=-5x-6 | | 22.27/3.4 | | 5-2x=x-7+3x | | x-Cos(x)=y | | -(7-4b)=4b-7 | | x-cosx=y | | 8=5v+3v |

Equations solver categories